Cortical Areas Associated With Multisensory Integration Showing Altered Morphology and Functional Connectivity in Relation to Reduced Life Quality in Vestibular Migraine - Zhe, Xia; Chen, Li; Zhang, Dongsheng; Tang, Min; Gao, Jie; Ai, Kai; Liu, Weijun; Lei, Xiaoyan; Zhang, Xiaoling (Frontiers in Human Neuroscience, 2021)
Background: Increasing evidence suggests that the temporal and parietal lobes are associated with multisensory integration and vestibular migraine. However, temporal and parietal lobe structural changes related to vestibular migraine need to be further investigated. Methods: Twenty-five patients with vestibular migraine (VM) and 27 age- and sex- matched healthy controls participated in this study. Participants completed standardized questionnaires assessing migraine and vertigo-related clinical features. Cerebral cortex characteristics (i.e., thickness [CT], fractal dimension [FD], sulcus depth [SD] and the gyrification index [GI]) were evaluated using an automated Computational Anatomy Toolbox (CAT12). The relationship between cortex characteristics and clinical features was also analyzed in the patients with VM. Results: Relative to controls, patients with VM showed significantly thinner CT in the bilateral inferior temporal gyrus, left middle temporal gyrus and the right superior parietal lobule (P < 0.05, corrected for family-wise error [FWE-corrected]). Additionally, a shallower SD was observed in the right superior and inferior parietal lobule (P < 0.05, FWE-corrected). FD and GI did not differ significantly between the two groups. A negative correlation was found between CT in the right inferior temporal gyrus (r = −0.542, P = 0.005), as well as the left middle temporal gyrus (r = −0.553, P = 0.004), and the dizziness handicap inventory score in VM patients. Conclusion: VM patients exhibited specific CT and SD changes in the temporal and parietal lobes. These structural differences might contribute to abnormalities in multisensory integration and vestbibular processing, suggesting that these regions play an important role in VM pathophysiology.